Organic amendments of soil and its effect on the NPK contents in rice plants grown on saline soil (Bangladesh Journal of Scientific and Industrial Research, 2018)
The potential and effectiveness of the indigenous organic amendments such as rice hull (RH), rice straw (RS) and sawdust (SD) at the rates of 0, 2 and 4 t ha-1, respectively on N, P and K contents of BRRI Dhan-47 grown on saline soil under variable moisture (field moist: FM and 2-5 cm standing water: SW) levels were evaluated in the field experiment. The N, P and K contents in the shoot at maturity stage of rice increased significantly (p